Influence Of Supervisory Control On Salesperson Performance: Examining The Role Of Adaptive Selling Behaviour As A Mediator - Kok, Leong Wong; Cheng, Ling Tan (Asian Academy of Management (AAM), 2016)
Salespersons are the key marketing agent and they play a signifcant role in determining business successes of frms. In today's highly competitive business environment, frms are attempting to outperform each other. Product quality and performance are no longer the key diﬀerentiating factor. The competitive edge of competing frms has shifted to the performance of the salespersons and the eﬀectiveness of managing them. Nevertheless, achieving salesperson performance remains as one of the most challenging tasks of sales management today. This study aims to examine the eﬀect of supervisory control on salesperson performance and the mediating role of salesperson's adaptive selling behaviour in the relationship between supervisory control and salesperson performance. Based on a sample of pharmaceutical salespersons in Malaysia, the results revealed that supervisory control of activity control has a signifcant positive relationship on salesperson performance, and adaptive selling behaviour signifcantly mediates the relationship between activity control and salesperson performance. Implications, limitations of the research and improvements for future studies were discussed.